A DEVELOPMENT OF BOTASI MEDIA BASED ON LOCAL WISDOM OF KEDIRI TO IMPROVE THE ABILITY TO DESCRIBE THE MESSAGE IN FAIRYTALES PRESENTED TO GRADE III STUDENTS OF WATUDANDANG STATE ELEMENTARY SCHOOL - Putri, Ardhita Candra Devi Santosa; Laila, Alfi; Nurlaila Zunaidah, Farida (Prodi Pendidikan Guru Sekolah Dasar, 2025)
This research was conducted with a background of problems obtained by conducting a needs analysis. The data collection technique used was data triangulation (observation, interviews, documentation). Data were collected in grade 3 of SD Negeri 3 Watudandang and SD Negeri 2 Watudandang in the Indonesian Language subject, the material of explaining the message in fictional narrative texts. From the observation results, it was found that grade 3 students still had difficulty in understanding the material. The difficulty in understanding the material of explaining the message in fictional narrative texts was because the learning did not use learning media. In addition, teacher-focused learning caused students to interact less with the material and get bored in learning. The above data is supported by the results of interviews with grade 3 teachers of SD Negeri 3 Watudandang and SD Negeri 2 Watudandang. Students tend to be more active in learning when using concrete-based learning media. Meanwhile, from the documentation data conducted by looking at the results of the learning evaluation, it was found that the average score of 3rd grade students of SD Negeri 3 Watudandang and SD Negeri 2 Watudandang on the material describing the message in fictional narrative text was 62. The score that was still below the KKTP indicated that the learning completion had not been achieved. The purpose of this study was to determine the validity, practicality, and effectiveness of BOTASI based on local wisdom on the material describing the message in fictional narrative text for 3rd grade students of SD Negeri 3 Watudandang and SD Negeri 2 Watudandang. The method used in this study was R&D with the ADDIE development model. The results of the media validity were 94.15%. The results of the practicality obtained were 100%. Meanwhile, the effectiveness of the media from the results of the learning evaluation got an average score of 86.25 in limited classes and 87.83 in large classes. From this, it can be concluded that the local wisdom-based BOTASI media for grade 3 students of SD Negeri 3 Watudandang and SD Negeri 2 Watudandang is declared very valid, very practical, and effective.